Incidence and Outcomes of Cardiopulmonary Resuscitation in ICUs: Retrospective Cohort Analysis. Issue 10 (14th June 2022) - Zajic, Paul; Hallmann, Barbara; Honnef, Gabriel; Fellinger, Tobias; Metnitz, Barbara; Posch, Martin; Rief, Martin; Zoidl, Philipp; Metnitz, Philipp G. H.
Abstract : OBJECTIVES: We aim to describe incidence and outcomes of cardiopulmonary resuscitation (CPR) efforts and their outcomes in ICUs and their changes over time. DESIGN: Retrospective cohort analysis. SETTING: Patient data documented in the Austrian Center for Documentation and Quality Assurance in Intensive Care database. PATIENTS: Adult patients (age ≥ 18 yr) admitted to Austrian ICUs between 2005 and 2019. INTERVENTIONS: None. MEASUREMENTS ANDN MAIN RESULTS: Information on CPR was deduced from the Therapeutic Intervention Scoring System. End points were overall occurrence rate of CPR in the ICU and CPR for unexpected cardiac arrest after the first day of ICU stay as well as survival to discharge from the ICU and the hospital. Incidence and outcomes of ICU-CPR were compared between 2005 and 2009, 2010 and 2014, and 2015 and 2019 using chi-square test. A total of 525, 518 first admissions and readmissions to ICU of 494, 555 individual patients were included; of these, 72, 585 patients (14.7%) died in hospital. ICU-CPR was performed in 20, 668 (3.9%) admissions at least once; first events occurred on the first day of ICU admission in 15, 266 cases (73.9%). ICU-CPR was first performed later during ICU stay in 5, 402 admissions (1.0%). The incidence of ICU-CPR decreased slightly from 4.4% between 2005 and 2009, 3.9% between 2010 and 2014, and 3.7% between 2015 and 2019 ( p < 0.001). A total of 7, 078 (34.5%) of 20, 499 patients who received ICU-CPR survived until hospital discharge. Survival rates varied slightly over the observation period; 59, 164 (12.0%) of all patients died during hospital stay without ever receiving CPR in the ICU. CONCLUSIONS: The incidence of ICU-CPR is approximately 40 in 1, 000 admissions overall and approximately 10 in 1, 000 admissions after the day of ICU admission. Short-term survival is approximately four out of 10 patients who receive ICU-CPR.